Reply to Storey et al.: More DNA and dating studies needed for ancient El Arenal-1 chickens - Gongora, J.; Rawlence, N.J.; Mobegi, V.A.; Alcalde, J.A.; Matus, J.T.; Hanotte, Olivier H.; Moran, C.; Austin, J.J.; Ulm, S.; Larson, G.; Cooper, A.; Han Jianlin (National Academy of Sciences, 2008)
In their letter, Storey et al. (1) concede that there is no direct genetic support for Polynesian–South American contact. However, they claim that linguistic, archaeological, and ethnohistoric evidence supports Polynesia as the most likely source of the El Arenal-1 chickens. We disagree on two grounds. First, such indirect evidence is conjectural, documents no eastward expansion to South America, and says nothing about the prehistoric availability of particular mtDNA haplotypes. Second, our central point was that analyses of all available ancient (2) and modern chicken mtDNA data reveal that the El Arenal-1 chicken carries a worldwide genetic signature potentially available to any of the possible introduction routes via Europe, Asia, and Polynesia (3). In contrast, none of the unusual genetic signatures from Easter Island chickens have been reported from South America (3).